2020
DOI: 10.3390/rs12030533
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Applications to Downscale GRACE-Derived Terrestrial Water Storage Data and to Fill Temporal Gaps

Abstract: The Gravity Recovery and Climate Experiment (GRACE) has been successfully used to monitor variations in terrestrial water storage (GRACETWS) and groundwater storage (GRACEGWS) across the globe, yet such applications are hindered on local scales by the limited spatial resolution of GRACE data. Using the Lower Peninsula of Michigan as a test site, we developed optimum procedures to downscale GRACE Release-06 monthly mascon solutions. A four-fold exercise was conducted. Cluster analysis was performed to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 79 publications
(93 reference statements)
0
26
0
Order By: Relevance
“…Jing et al (2020) reconstructed the GRACE TWSA by using the RF regression model combined with an SMW structure, the LR model, and the GLDAS, and found the RF model outperforms the LR model. Sahour et al (2020) applied the multivariate regression (MR), ANN, and XGBoost approaches to fill the GRACE in the time series data over the Lower Peninsula of Michigan during 2002-2016 and found that the XGBoost model outperformed the MR and ANN.…”
Section: Comparison Of Time-series Water Storage Reconstruction Resulmentioning
confidence: 99%
“…Jing et al (2020) reconstructed the GRACE TWSA by using the RF regression model combined with an SMW structure, the LR model, and the GLDAS, and found the RF model outperforms the LR model. Sahour et al (2020) applied the multivariate regression (MR), ANN, and XGBoost approaches to fill the GRACE in the time series data over the Lower Peninsula of Michigan during 2002-2016 and found that the XGBoost model outperformed the MR and ANN.…”
Section: Comparison Of Time-series Water Storage Reconstruction Resulmentioning
confidence: 99%
“…However, empirical approaches using machine learning (ML) have been used for a flexible fusion of datasets with highly different features [28,29]. The fundamental process involves ML training with matched pairs between different types of data and then using the training results to predict spatially high-resolution but temporally low-resolution data from counterpart data (temporally high-resolution but spatially low-resolution).…”
Section: Introductionmentioning
confidence: 99%
“…Although data assimilation methods remain consistent in the physical process, some shortcomings still require to be considered [ 25 ]. The implementation of data assimilation is relatively complicated [ 26 ], and its accuracy is subject to the full error covariance matrix of GRACE observations and hydrological models [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial neural networks (ANNs) have the capabilities of simulating complex hydrological characteristics to an arbitrary degree of accuracy [ 34 , 35 ]. This makes ANN becomes an attractive measure in the downscaling researches, which have been applied to some typical regions, e.g., the Northern High Plains [ 36 ], California’s Central Valley [ 34 ], and the Lower Peninsula of Michigan [ 26 ]. Similarly, some tree-based machine learning algorithms (e.g., random forest (RF) and gradient boosting decision tree (GBDT)) become popular in regression tasks with the advantages of simplicity and effectiveness.…”
Section: Introductionmentioning
confidence: 99%